2016
DOI: 10.1289/ehp158
|View full text |Cite
|
Sign up to set email alerts
|

Urban Dust Microbiome: Impact on Later Atopy and Wheezing

Abstract: Background:Investigations in urban areas have just begun to explore how the indoor dust microbiome may affect the pathogenesis of asthma and allery.Objective:We aimed to investigate the early fungal and bacterial microbiome in house dust with allergic sensitization and wheezing later in childhood.Methods:Individual dust samples from 189 homes of the LISAplus birth cohort study were collected shortly after birth from living room floors and profiled for fungal and bacterial microbiome. Fungal and bacterial diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 32 publications
(38 reference statements)
1
35
0
1
Order By: Relevance
“…However, while increased levels of β-1,3-glucan may certainly indicate greater fungal concentrations, it may also represent a more diverse fungal population. In fact, exposure to greater fungal diversity offered protection against sensitization to aeroallergens and early childhood wheeze in a German longitudinal birth cohort, mirroring the protective effects of microbial diversity in the human microbiome 102 . Importantly, the predictive effect of fungal exposure on asthma development seems to occur independently of fungal sensitization.…”
Section: Indoor Allergen Exposurementioning
confidence: 85%
“…However, while increased levels of β-1,3-glucan may certainly indicate greater fungal concentrations, it may also represent a more diverse fungal population. In fact, exposure to greater fungal diversity offered protection against sensitization to aeroallergens and early childhood wheeze in a German longitudinal birth cohort, mirroring the protective effects of microbial diversity in the human microbiome 102 . Importantly, the predictive effect of fungal exposure on asthma development seems to occur independently of fungal sensitization.…”
Section: Indoor Allergen Exposurementioning
confidence: 85%
“…We have previously shown in this cohort that the quantity of exposure to bacterial and fungal cell-wall components in early life has a bell-shaped association with asthma at the age of 6 years. 9 Studies with DNA-based methods have indicated that the asthmaprotective characteristics might include diversity [10][11][12][13] or, more specifically, diversity within certain taxa and a lack of predisposing microbes. [14][15][16][17] However, it remains unclear whether there are specific individual taxa in the indoor microbiome that are independently associated with reduced asthma risk.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…For example, Tischer et al [32 ▪▪ ] found that exposure to higher fungal diversity shortly after birth was associated with a decreased risk of developing wheezing and aeroallergen sensitization in later childhood. Future work should continue to evaluate the role of fungal diversity on the development of atopic conditions.…”
Section: Mold Exposure and Asthmamentioning
confidence: 99%